ARTIFICIAL INTELLIGENCE (AI) IN SUPPORTING SENIOR HIGH SCHOOL STUDENTS' MULTIMODAL TEXT PRODUCTION - HIDAYAT, R RIZKIKI AZKIA; HIDAYAT, RADEN AULIA UTAMI (English Language, Linguistics, and Culture International Journal, 2024)
In the digital age, integrating artificial intelligence (AI) into educational practices has revolutionized students' capabilities in producing multimodal texts, which encompass a diverse range of communicative forms, including text, images, audio, video, and interactive content. This study explores the multifaceted role of AI in supporting students' multimodal text production. It examines how AI-driven tools and platforms facilitate content generation, provide personalized feedback, enhance collaborative efforts, and improve accessibility for diverse learners. The participants of this study were an English teacher and her students at one of the public senior high schools in West Java, Indonesia. A qualitative design in the form of a case study was selected as the methodology. Classroom observation and interviews were employed to collect the data. Through a comprehensive analysis of current AI applications such as Grammarly, Chat-GPT, and Canva, this paper highlights the transformative potential of AI in enhancing students' creativity, technical proficiency, and academic success. The findings suggest that AI not only aids in the efficient creation and refinement of multimodal texts but also fosters a more inclusive and adaptive learning environment. This study underscores the importance of integrating AI technologies into educational curricula to equip students with the necessary skills to thrive in a multimodal and increasingly digital world.